A revision of the genus Ora Clark, 1865 (Coleoptera: Scirtidae) in Argentina (part II)-redescriptions, updated distributions and a key to species - Libonatti, María Laura (2015)
This second part of the revision of the Argentine species of Ora Clark, 1865 provides detailed redescriptions, habitus photos, illustrations of male and female genitalia for eight species, an identification key and updated distributions for all the species. A lectotype is hereby designated for Ora bruchi Pic, 1928. Scirtes brevenotatus v. mediolineatus Pic, 1928 and S. brevenotatus wagneri Pic, 1928 are here raised to species level and transferred to Ora. The females of Ora atroapicalis, O. depressa, O. mediolineata, O. platensis, O. semibrunnea and O. wagneri are described. Ora bivittata Pic, 1922 is newly recorded from Argentina and several provincial records are added to the geographical range of early known species. Eleven species of Ora are now recognized to occur in Argentina: O. atroapicalis Pic, 1928, O. bivittata Pic, 1922, O. brevieminentia Libonatti, 2014, O. bruchi Pic, 1928, O. depressa (Fabricius, 1801), O. mediolineata (Pic, 1928) comb. n., O. megadepressa Libonatti, 2014, O. platensis Brèthes, 1925, O. semibrunnea Pic, 1922, O. sigmoidea Libonatti, 2014 and O. wagneri (Pic, 1928) comb. n.